Pengaruh Kualitas Produk, Harga, Promosi terhadap Kepuasan Konsumen Minyak Angin V-Fresh Aromatheraphy pada PT. Eagle Indo Pharma - Chelsa Audi Mahira; Lamtota Togatorop; Simon Ginting; Jessica Apriani Simbolon; Juniarlina Sianipar; Fenny Krisna Marpaung (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The results of hypothesis testing show that partially known for the product quality variable is 2,967. Because t count 2,967 > t table 1.98, it can be concluded that Ha is accepted and H0 is rejected. Partially for the price variable is 4.087. Because t count 4.087 ˃ t table 1.98, it can be concluded that Ha is accepted and H0 is rejected. Partially for the promotion variable is 0,943. Because t count 0,943 < t table 1.98, it can be concluded that H0 is accepted and Ha is rejected. For the results of the F test, it was obtained that the Sig <0.05 was 0.000. Then the hypothesis is accepted or product quality (X1), price (X2) and promotion (X3) simultaneously have an effect on customer satisfaction (Y).